Alpha - Beta (α and β) Diversity Assessment of the Mangroves of Two Districts along the Coast of Maharashtra State - Kulkarni, N A; Bhosale, L J (Plantae Scientia, 2021)
Alpha-Beta Diversity (α and β): During the present study the alpha and beta diversity of mangrove in the study area has been analyzed. Twenty-nine estuaries from Ratnagiri and Sindhudurg districts of Maharashtra State are studied and data analyzed for calculating alpha and beta diversity.